Legume Intercropping With the Bioenergy Crop Sida hermaphrodita on Marginal Soil - Nabel, Moritz; Schrey, Silvia D.; Temperton, Vicky M.; Harrison, Lucy; Jablonowski, Nicolai D. (Frontiers in Plant Science, 2018)
The cultivation of perennial biomass plants on marginal soils can serve as a sustainable alternative to conventional biomass production via annual cultures on fertile soils. Sida hermaphrodita is a promising species to be cultivated in an extensive cropping system on marginal soils in combination with organic fertilization using biogas digestates. In order to enrich this cropping system with nitrogen (N) and to increase overall soil fertility of the production system, we tested the potential of intercropping with leguminous species. In a three-year outdoor mesocosm study, we intercropped established S. hermaphrodita plants with the perennial legume species Trifolium pratense, T. repens, Melilotus albus and Medicago sativa individually to study their effects on plant biomass yields, soil N, and above ground biomass N. As a control for intercropping, we used a commercial grass mixture without N2-fixing species as well as a no-intercropping treatment. Results indicate that intercropping in all intercropping treatments increased the total biomass yield, however grass species competed with S. hermaphrodita for N more strongly than legumes. Legumes enriched the cropping system with fixed atmospheric nitrogen (N2) and legume facilitation effects varied between the legume species. T. pratense increased the biomass yield of S. hermaphrodita and increased the total biomass yield per mesocosm by 300%. Further, the total above ground biomass of S. hermaphrodita and T. pratense contained seven times more N compared to the mono-cropped S. hermaphrodita. T. repens also contributed highly to N facilitation. We conclude that intercropping of legumes, especially T. pratense and T. repens can stimulate the yield of S. hermaphrodita on marginal soils for sustainable plant biomass production.